2015
DOI: 10.1097/mib.0000000000000268
|View full text |Cite
|
Sign up to set email alerts
|

Immunochip Analysis Identification of 6 Additional Susceptibility Loci for Crohnʼs Disease in Koreans

Abstract: Background Crohn's disease (CD) is an intractable inflammatory bowel disease of unknown cause. Recent genome-wide association studies of CD in Korean and Japanese populations suggested marginal sharing of susceptibility loci between Caucasian and Asian populations. As the 7 identified loci altogether explain 5.31% of the risk for CD, the objective of this study was to identify additional CD susceptibility loci in the Korean population. Methods Using the ImmunoChip custom single-nucleotide polymorphism array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 35 publications
7
64
0
Order By: Relevance
“…rs1250550 was found to be an early-onset IBD-specific SNP in the region of ZMIZ1 [29, 30]. rs1250569 which lies within ZMIZ1, was also found to be a susceptibility locus for CD in Koreans [9]. Our data support the notion that there is an association between rs1250569 and susceptibility to early-onset Crohn’s disease.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…rs1250550 was found to be an early-onset IBD-specific SNP in the region of ZMIZ1 [29, 30]. rs1250569 which lies within ZMIZ1, was also found to be a susceptibility locus for CD in Koreans [9]. Our data support the notion that there is an association between rs1250569 and susceptibility to early-onset Crohn’s disease.…”
Section: Discussionsupporting
confidence: 79%
“…Recently, an immuno-chip analysis of a Korean population identified rs1250569 in zinc finger MIZ-type containing 1 (ZMIZ1) as a novel susceptibility locus for Crohn's disease that increased susceptibility in an Asian population [9]. rs1042522, in tumour protein p53 (TP53), has previously been observed in a variety of cancers and associated with an increased risk of IBD in Canadians [10].…”
Section: Introductionmentioning
confidence: 99%
“…We next examined the potential associations of type I Paneth cell phenotype with 56 SNPs, selected based on known CD susceptibility associations (3,5,(21)(22)(23)(27)(28)(29) or known association with Paneth cell function (17) (Supplemental Table 3). These SNPs include coding variants for ATG16L1 (T300A) associated with Paneth cell defects in North American CD cohorts and in genetic mouse models (18,19,30).…”
Section: Resultsmentioning
confidence: 99%
“…For genotype-Paneth cell defect correlation, we first adopted a hypothesis-driven approach with selected SNPs (Figure 1). These SNPs include: (a) 45 SNPs shown to have CD-specific susceptibility from an ImmunoChip study examining European ancestry CD (3); (b) an additional 38 SNPs reported in European and East Asian ancestry CD (5); (c) 14 SNPs associated with East Asian (Japanese and/or Korean) CD through GWAS analyses (21,23,28,77) and deep-resequencing analysis (22); and (d) 2 functional CD-associated variants that were either reported to be associated with Paneth cell defect in our previous studies (18,19), or whose genes involved had been implicated to be associated with Paneth cell biology in preclinical studies (17,29). By excluding duplicates, a total of 73 SNPs were compiled as candidates.…”
Section: Methodsmentioning
confidence: 99%
“…To replicate and fine map risk loci identified in genome-wide association studies (GWAS) of autoimmune and inflammatory disorders such as RA, the Immunochip Consortium designed the Immunochip (iChip), a custom Illumina Infinium high-density array that has been used to study RA in patients of several racial and ethnic backgrounds (4)(5)(6)(7)(8). Using the iChip and many other arrays, 100 RA risk loci of genome-wide significance (p < 5 × 10 -8 ) have been identified in individuals of European and and permanent disability (1).…”
mentioning
confidence: 99%